The Impact of Financial and Operating Leverage on Profitability of Industrial Companies listed on Saudi Stock Exchange Market (During 2017-2021) - Ahmed, Ahmed Hashim (Journal of Economic, Administrative and Legal Sciences, 2023)
The purpose of this study is to determine the impact of operating and financial leverage on profit margin, return on assets, return on equity, and market price per share of industrial companies listed on the Saudi stock market. The study adopts deductive, inductive and historical methods.  The results of the study showed that there is an impact of operational leverage on rate of return on equity and profit margin, and also there is an impact of financial leverage on return on equity, return on assets, and profit margin, while the results of the study proved that there is no impact of operational leverage on the return on assets of Saudi industrial companies under study.
Keywords: financial leverage; operating leverage; profit margin; return on assets; return on equity; market price per share